Crop straw-derived biochar alleviated cadmium and copper phytotoxicity by reducing bioavailability and accumulation in a field experiment of rice-rape-corn rotation system. (October 2021) - Zong, Yutong; Xiao, Qing; Malik, Zaffar; Su, Yuan; Wang, Yefeng; Lu, Shenggao
Abstract: Biochar has the potential to control the bioavailability and transformation of heavy metals in soil, thereby ensuring the safe crop production. A three seasons field experiment was conducted to investigate the effect of crop straw-derived biochar on the bioavailability and crop accumulation of Cd and Cu in contaminated soil. Wheat straw biochar (WSB), corn stalk biochar (CSB), and rice husk biochar (RHB) were applied at the rate of 0, 1.125, and 2.25 × 10 4 kg ha −1, respectively. The results showed that all types of biochar significantly increased soil pH, organic carbon and cation exchangeable capacity (CEC), compared to the control. The reduction in DTPA extractable Cd and Cu contents was much greater under high dosage biochar application, with a prominence at RHB treatment throughout the three cropping seasons, compared to the control. Moreover, the biological accumulation of Cd and Cu in the grains of rapeseed and corn significantly decreased after biochar application. Linear regression also confirmed the effective role of biochar in controlling the translocation and accumulation of Cd and Cu due to their inactive bioavailability. In addition, the sequential extraction indicated that exchangeable fraction (EXF) of Cu and Cd had decreased, while residual fraction (RSF) had increased under all biochar amendments. Contrarily, the oxidizable fraction (OXF) of Cd decreased while OXF of Cu increased under biochar treatments. Biochar application, especially RHB, could be an effective measure to enhance Cd and Cu adsorption and immobilization in polluted soils and thereby reducing its uptake and translocation to crops. Graphical abstract: Image 1 Highlights: Biochar significantly increased soil pH, SOC, CEC and immobilized soil Cd and Cu. Biochar application significantly reduced the bioavailability of Cd and Cu. The exchangeable fraction Cd and Cu decreased and residual fraction increased after biochar amended. Biochar restricted Cd and Cu primarily due to precipitation, physical sorption, surface electrostatic, and complexation.